Zike Martha Public Relations and Transformation of Social Security Health Services Building Solid Community Relations: - - zike martha (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
ABSTRACT This study explores the role of Public Relations (PR) in building Community Relations and improving the quality of healthcare services for social security providers in Sawahlunto, West Sumatra. The research aims to analyze how PR practices influence community trust and the accessibility of healthcare services in this mining region. Using a qualitative approach, data was collected through in-depth interviews with key informants, including PR professionals and local community leaders. The results indicate that effective PR strategies can enhance public awareness of health services, increase community participation, and build stronger relationships between stakeholders. The study concludes that PR plays a crucial role in promoting healthcare services and addressing community concerns, which ultimately contributes to better healthcare outcomes. Keywords: Community Relations, Public Relations, Healthcare Services, Social Security, Mining Sector